PILIHAN STUDI LANJUT SISWA SMK: ANTARA MOTIVASI DAN MINAT - Fauziah, Neneng (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Continuing to a higher school level is the dream of students. Vocational high school (SMK) graduates hope to develop their potential in universities with study programs that are of interest. The learning motivation of students with an interest in continuing their education to college is still not by the dreams of students. This study used quantitative methods with a population in this study of 76 students. Data collection techniques were carried out using observation methods, distributing questionnaires to grade XII students of Karya Guna Bhakti 2 Vocational High School (SMK) Bekasi City. Relating student learning motivation to college can be realized as expected, and it needs the role of students and parents, in other words, student learning motivation gets internal and external encouragement to make behavior changes and several other indicators that have a big role in student success in learning. Interest in continuing education to college is influenced by several factors including factors from within oneself, school environment factors, family environment factors, and study program factors chosen to continue education. The results of the questionnaire distributed to class XII students are quite high interest in continuing their studies at university, but from the results of statistical tests obtained a value of p = 0.14, it can be concluded that there is no significant relationship between learning motivation and interest in continuing studies.